2015
DOI: 10.3389/fonc.2015.00286
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Complete Response and Disease Recurrence Following Chemoradiation for Rectal Cancer

Abstract: ObjectiveApproximately 10–40% of rectal patients have a complete response (CR) to neoadjuvant chemoradiation (CRT), and these patients have improved survival. Thus, non-operative management (“watch-and-wait” approach) may be an option for select patients. We aimed to identify clinical predictors of CR following CRT.MethodsPatients treated with definitive CRT for T3–T4, locally unresectable T1–T2, low-lying T2, and/or node-positive rectal cancer from August 2004 to February 2015 were retrospectively reviewed. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 40 publications
8
43
1
Order By: Relevance
“…Another RCT 59 corroborated these findings. Two previous meta-analyses 10,60 found that the length of the interval between nCRT and surgery was an independent predictor of pCR. Kalady et al 61 even demonstrated that a longer waiting time between nCRT and surgery was the single most important determinant of pCR.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another RCT 59 corroborated these findings. Two previous meta-analyses 10,60 found that the length of the interval between nCRT and surgery was an independent predictor of pCR. Kalady et al 61 even demonstrated that a longer waiting time between nCRT and surgery was the single most important determinant of pCR.…”
Section: Discussionmentioning
confidence: 90%
“…Another RCT corroborated these findings. Two previous meta‐analyses found that the length of the interval between nCRT and surgery was an independent predictor of pCR. Kalady et al .…”
Section: Discussionmentioning
confidence: 97%
“…Clinical factors, including tumor size, clinical T and N stages, distance of tumor from the anal verge, and interval from nCRT to surgery, are associated with response to nCRT in rectal cancer [19,20,21,22,23]. In addition, some pathological features have been shown to predict the response to nCRT.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some pathological features have been shown to predict the response to nCRT. Tumor differentiation, circumferential tumor, mucinous histology and the presence of macroscopic ulceration are associated with poor response to nCRT [20,21,22,23,24]. Imaging modalities including positron emission tomography-computed tomography, magnetic resonance imaging (MRI) and endoscopic ultrasound are currently used for pretreatment staging, assessment of response to nCRT, and restaging after nCRT [25,26,27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The NCCN has a guideline for locally advanced rectal cancer proposing that CRT be followed by total mesorectal excision (TME) 1) . Pathological complete response (pCR) rates have been reported to range from 10 to 40% 2) . Maas et al demonstrated that achievement of pCR is associated with an improved outcome 3) .…”
Section: Introductionmentioning
confidence: 99%